Approach of 2D direction of arrival estimation of FMCW traffic radar by utilising 1D array. Issue 2 (1st January 2020) - Zhang, Wei; He, Ningyu; He, Zishu; Han, Minghua
Abstract : The frequency‐modulated continuous wave (FMCW) radar will play a more important role in future intelligent traffic systems due to low cost and high adaptability to complex environments. Generally, a 2D array is utilised to measure range, speed and azimuth and elevation angles (4D) for multiple vehicles simultaneously. However, a traffic radar utilising a 2D array will enhance its system complexity; therefore, the increased cost would make it less superior to LiDAR. In this Letter, an azimuth and elevation angles estimation method of FMCW radar utilising only 1D array is proposed. Thus, it can provide 4D parameters to multiple vehicles simultaneously. The feasibility of the proposed approach is verified by on‐road measurement data.